State and territory government strategic plans: Exercises in managing, monitoring and marketing - McMahon, Lance; Phillimore, John (Blackwell Publishing Asia P/L, 2013)
All but three of the Australian States and Territories have whole-of-government, jurisdiction- wide strategic plans in place and the three exceptions had previously established a state plan in the decade after the first such plans were introduced by Tasmania and Victoria in 2001. Scholarly attention to date has been directed towards discrete aspects of state plans, such as the extent to which they can be seen as exercises in participative democracy or sustainability, rather than with examining state plans for what they explicitly purport to be – strategic plans originating in the core executive of government. We propose that there are three key strategic orientations for Australian state plans: to holistically manage, monitor and market government administration. These orientations may be competing, complementary or overlapping, and can vary over time. The article also proposes that state plans are a significant development in public management and warrant further and more detailed examination.